Protecting real estate cultural property to ensure its sustainability in Algerian legislation - Hassina, Ghaoues (The International tax journal, 2025)
Algeria possesses a rich cultural heritage, the result of the succession of many civilizations. This heritage is embodied in its material aspect in real cultural property, but the latter is exposed to several dangers that threaten its existence and being. Therefore, the Algerian legislator sought to establish appropriate legal frameworks to protect it in accordance with what is stated in Law 98/44 related to the protection of cultural heritage, by devoting institutional and administrative protection to preserve it, value it and achieve its sustainability for the benefit of future generations It was embodied in the installation of central and local institutions to undertake this and the enactment of qualitative measures and procedures represented in registering these properties in the additional inventory list, classifying them or creating them in the form of preserved sectors, in addition to developing plans to protect them and imposing the condition of prior authorization as a preventive administrative measure. However, this protection remains relative in view of the difficulties that afflict the application of the law on the ground.